2016
DOI: 10.1016/j.jtcvs.2016.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Open surgical repair of multiple tuberculous mycotic aneurysms of the thoracoabdominal aorta

Abstract: Multiple tuberculous aneurysms of the thoracoabdominal aorta extending to the aortic bifurcation. Central MessageMultiple tuberculous mycotic aneurysms of the thoracoabdominal aorta involving the aortic arch are rare. We report the case of an 18year-old man with this condition who was treated successfully.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Traditionally, surgical intervention for mycotic aneurysms involves excision of infected tissues and vessel reconstruction via extra-anatomic bypass or in situ reconstruction. 6,7 Despite risk of infection of vascular prosthetic graft, both methods of surgical management conferred similar and excellent results with adequate ATT. 4 Canaud et al described favorable outcome in all three patients on follow-up (6 months, 8 years, and 10 years, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…Traditionally, surgical intervention for mycotic aneurysms involves excision of infected tissues and vessel reconstruction via extra-anatomic bypass or in situ reconstruction. 6,7 Despite risk of infection of vascular prosthetic graft, both methods of surgical management conferred similar and excellent results with adequate ATT. 4 Canaud et al described favorable outcome in all three patients on follow-up (6 months, 8 years, and 10 years, respectively).…”
Section: Discussionmentioning
confidence: 98%
“…The patient showed good clinical recovery on follow-up with functioning aortic prosthesis. Velayudhan et al [ 38 ] (2016) reported a case in which the patient with TBAA recovered well after open surgical repair. Dilangalen et al [ 39 ] (2017) reported a case of infectious aortitis with complaint of abdominal pain.…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the Journal, Velayudhan and colleagues 1 report on the surgical treatment of a relatively rare but important cause of aortic aneurysm, tuberculosis. 1 Treatment of this condition is of particular importance in countries such as India, the source of this report, where tuberculosis remains a major health problem. Velayudhan and colleagues 1 successfully replaced the distal arch and the entire descending thoracic and abdominal aorta of an 18-year-old male patient with multiple presumed pseudoaneurysms as well as occlusion of the left subclavian, right renal, and inferior mesenteric arteries.…”
Section: Nicholas T Kouchoukos MDmentioning
confidence: 99%